A cadaveric study for structural variations of the stomach - Yesupadam, K. .; Devi, K. V. N. Geetha; Lakshmi, V. V. V. (International Journal of Research in Medical Sciences, 2017)
Background: The morphology of the stomach taken for the study for its clinical interventions like gastro-oesophagial reflux disorders (GERD) which are very common nowadays because of unusual timing of eating food, stress related jobs, eating of junk foods etc. The obesity now considered to be the 2nd leading cause of death, which can be prevented by gastric reconstructive procedures i.e., the bariatric surgeries. Methods: The study includes 70 adult cadavers, 28 obtained from the formalin fixed specimens kept for anatomy dissection for 1st year MBBS students from 2009 batch to 2015 batch. The remaining 42 specimens obtained from the postpartum bodies in the Forensic department of Guntur Medical College, Guntur. The abdominal cavity opened according to the incisions in the Cunninghams manual of anatomy. Stomach identified by reflecting anterior abdominal wall. Location noted, shape observed, Length taken, relations blood supply noted, results tabulated. Results: 71.4% specimens are “J” shaped, 14.2% are reverse “L” shaped, 7.2% are cresentic shaped, 7.2% are cylindrical shaped observed. The length is more in “J” shaped specimens. The lower extent of greater curvature at L3 in 71.4% specimens, at L2 in 21.4% specimens, at L4 in 7.2% specimens. Conclusions: The present study discussed about the shape of the stomach and the majority of specimens shown “J” shape. Remaining are reverse “L” shape; cresentic and cylindrical shaped.